The Relation of Inflammaging With Skeletal Muscle Properties in Elderly Men. Issue 2 (April 2019) - Zembron-Lacny, Agnieszka; Dziubek, Wioletta; Wolny-Rokicka, Edyta; Dabrowska, Grazyna; Wozniewski, Marek
Aging is associated with a progressive decline of muscle mass and/or the qualitative impairment of the muscle tissue. There is growing evidence of the prominent role of low-grade chronic inflammation in age-related changes in the neuromuscular system. The purpose of the study was to identify the inflammatory mediators responsible for deficit in functional fitness and to explain whether inflammation is related to changes in body composition and the decline of muscle strength in older men. Thirty-three old-aged males (73.5 ± 6.3 years) and twenty young-aged males (21.2 ± 1.3 years) participated in the study. The body composition (bioelectrical impedance analysis), functional capacity (6-min walking test) and knee extension strength (isokinetic test) were estimated. In serum, circulating inflammatory markers H2 O2, IL-1β, TNFα, and hsCRP as well as growth factors IGF-I and PDGF BB concentrations were determined (immunoenzymatic methods). The concentrations of H2 O2, IL-1β, TNFα, and hsCRP were significantly higher in older than young men. The growth factors IGF-I and PDGF BB were twofold lower and related to high levels of IL-1β and TNFα in the elderly. The changes in cytokines and growth factors levels were correlated with age and peak torque (TQ at 60°/s and 180°/s) in the knee extension. The result of the 6-min walking test was inversely correlated with fat mass index (FMI, r = −.983; p < .001). The generation of inflammatory mediators in older men was related to changes in body composition, maximum strength muscle, and age-related changes in skeletal muscle properties responsible for deficit in functional fitness.